National Beef Quality Audit–2016: Transportation, mobility, live cattle, and carcass assessments of targeted producer-related characteristics that affect value of market cows and bulls, their carcasses, and associated by-products - Harris, M. K. (Transl Anim Sci, 2017)
The National Beef Quality Audit–2016 marks the fourth iteration in a series assessing the quality of live beef and dairy cows and bulls and their carcass counterparts. The objective was to determine the incidence of producer-related defects, and report cattle and carcass traits associated with producer management. Conducted from March through December of 2016, trailers (n = 154), live animals (n = 5,470), hide-on carcasses (n = 5,278), and hide-off hot carcasses (n = 5,510) were surveyed in 18 commercial packing facilities throughout the United States. Cattle were allowed 2.3 m(2) of trailer space on average during transit indicating some haulers are adhering to industry handling guidelines for trailer space requirements. Of the mixed gender loads arriving at processing facilities, cows and bulls were not segregated on 64.4% of the trailers surveyed. When assessed for mobility, the greatest majority of cattle surveyed were sound. Since the inception of the quality audit series, beef cows have shown substantial improvements in muscle. Today over 90.0% of dairy cows are too light muscled. The mean body condition score for beef animals was 4.7 and for dairy cows and bulls was 2.6 and 3.3, respectively. Dairy cattle were lighter muscled, yet fatter than the dairy cattle surveyed in 2007. Of cattle surveyed, most did not have horns, nor any visible live animal defects. Unbranded hides were observed on 77.3% of cattle. Carcass bruising was seen on 64.1% of cow carcasses and 42.9% of bull carcasses. However, over half of all bruises were identified to only be minor in severity. Nearly all cattle (98.4%) were free of visible injection-site lesions. Current results suggest improvements have been made in cattle and meat quality in the cow and bull sector. Furthermore, the results provide guidance for continued educational and research efforts for improving market cow and bull beef quality.